2023
DOI: 10.1108/neje-10-2022-0095
|View full text |Cite
|
Sign up to set email alerts
|

Ideology and ethics of transitional entrepreneurs: legitimacy, soft law, and overcoming a distressed economy

Abstract: PurposeTransitional entrepreneurship in distressed economies is a fairly new concept with respect to new ventures in such challenging economic environments. Formal institutional voids are sometimes held up as a reason for the difficulties present in distressed economies, along with exogenous shocks and other upheavals. In this research, the authors seek to contribute empirically and theoretically as to ways in which formal institutions voids can be filled by a culture developed by transitional entrepreneurs. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…In this second evaluation process, 14 papers from RQ2 and 4 from RQ3 were excluded. The SLR made it possible to define indicators and indices to be implemented in the proposed framework [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127]. The corruption risk was distinguished into various se ings, all of which were directly correlated to political instability and to ideological differences that create religious and political tensions, generating a high degree of instability.…”
Section: Corruptionmentioning
confidence: 99%
“…In this second evaluation process, 14 papers from RQ2 and 4 from RQ3 were excluded. The SLR made it possible to define indicators and indices to be implemented in the proposed framework [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127]. The corruption risk was distinguished into various se ings, all of which were directly correlated to political instability and to ideological differences that create religious and political tensions, generating a high degree of instability.…”
Section: Corruptionmentioning
confidence: 99%
“…The final two papers illustrate how transitional entrepreneurs contribute to their communities and manage through the challenges of difficult and distressed economies. Khosravi et al (2023) in their paper, titled “ Ideology and ethics of transitional entrepreneurs: Legitimacy, soft law, and overcoming a distressed economy ,” discuss how transitional entrepreneurs help fill formal institutional voids through their contributions to the development of informal business norms. The authors conduct a thematic analysis using interviews with Iranian entrepreneurs and economists to illustrate how transitional entrepreneurs navigate a distressed economy to build a culture (and attract support from government and allied organizations such as banks) that encourages and legitimizes innovation and new venture creation, given the importance of ideas and informal institutions in encouraging entrepreneurship at all levels (cf.…”
Section: Special Issue: Transitional Entrepreneurshipmentioning
confidence: 99%
“…Whether it is a veteran suffering from post-traumatic stress disorders (PTSD) or an entrepreneur facing social stigma due to their gender, station or prior incarceration, transitional entrepreneurs face significant adversities in launching and running their businesses. See, as examples, Khosravi et al .’s (2023) discussion of entrepreneurs in challenging and isolated environments without supportive institutions and Sun's (2023) description of entrepreneurs navigating difficult circumstances in a refugee camp.…”
Section: Emergent Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, with the continuous development of social development ne eds and professional growth needs of college students, "innovation and entrepreneurship" education for college students should also be adjusted in a timely manner in terms of educational concepts, models and methods [38][39][40][41]. This is demonstrated by numerous entrepreneurship courses emphasizing skills typically associated with management and business planning [42][43][44]. However, it is suggested that these courses should encompass creative skills, such as receptiveness to change, problem -solving approaches, risk-taking, and particularly teamwork [45,46].…”
Section: Introductionmentioning
confidence: 99%